Alternative solutions to airport saturation: Simulation models applied to congested airports - Alfonso Herrera García (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2017)
This paper explores several methods for coping with excess demand at airports through applying simulation modeling that focusses on how to use the existing airport infrastructure more efficiently. The introduction presents an overview of the importance of solving the airport saturation problem and sets out several approaches to solutions, which are divided into four distinct groups, or options. The fourth option applies operational practices and/or new technology to improve the airport procedures, including computer modeling and simulation. The document presents the application of simulation models to the capacity issues at the Mexico City Airport to demonstrate how to potentially alleviate congestion. Examples include redistribution of takeoffs and landings to increase runway capacity; reduction of air traffic movements through allowing operations of aircraft with greater capacity; deployment of new technologies to increase runway capacity; and by means of new operational procedures, changing the aircraft waiting sequence to reduce delays
Keywords: 330; Flughafeninfrastruktur; Verkehrsaufkommen; Simulation